2004
DOI: 10.1111/j.1365-2125.2003.02041.x
|View full text |Cite|
|
Sign up to set email alerts
|

Database analyses for the prediction of in vivo drug–drug interactions from in vitro data

Abstract: AimsIn theory, the magnitude of an in vivo drug-drug interaction arising from the inhibition of metabolic clearance can be predicted using the ratio of inhibitor concentration ([I]) to inhibition constant ( K i ). The aim of this study was to construct a database for the prediction of drug-drug interactions from in vitro data and to evaluate the use of the various estimates for the inhibitor concentrations in the term [I]/ K i . MethodsOne hundred and ninety-three in vivo drug-drug interaction studies involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
240
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(246 citation statements)
references
References 15 publications
2
240
1
1
Order By: Relevance
“…2A). This contrasts somewhat with a previous report , which estimated correctly the in vivo magnitude of the quinidine interaction with desipramine, metoprolol, and imipramine using an external database (Ito et al, 2004). Interrogation of the two datasets indicates that a minor (ϳ2-fold) difference in both fu b and K i values results in the ϳ4-fold difference in ␦AUC prediction.…”
Section: Estimation Of Fraction Metabolized By Individual Major Humancontrasting
confidence: 51%
“…2A). This contrasts somewhat with a previous report , which estimated correctly the in vivo magnitude of the quinidine interaction with desipramine, metoprolol, and imipramine using an external database (Ito et al, 2004). Interrogation of the two datasets indicates that a minor (ϳ2-fold) difference in both fu b and K i values results in the ϳ4-fold difference in ␦AUC prediction.…”
Section: Estimation Of Fraction Metabolized By Individual Major Humancontrasting
confidence: 51%
“…The unbound concentration of an inhibitor is usually applied in this respect. However, it has been suggested that, at least for metabolic interactions, it may be more appropriate to use the total concentration in these calculations (Ito et al, 2004;Bachmann and Lewis, 2005). In this study, estimates based on total CsA concentrations show that the degree of OATP1B1 PS int inhibition would be more than 94% throughout the dosing interval, with a maximum of 99% (Fig.…”
Section: Cyclosporine a But Not Tacrolimus Inhibits Oatp1b1mentioning
confidence: 87%
“…In addition, previous findings have shown spontaneous nonenzymatic hydrolysis (Schumacher et al, 1965). To address the inhibitory potential of a drug, it was considered important to determine an inhibition constant (K i ) (Ito et al, 2004). However, there is little information about inhibition by thalidomide thus far.…”
mentioning
confidence: 99%